1990
DOI: 10.2134/jeq1990.00472425001900030020x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Field‐Grown Soybean in Response to Enhanced Exposure to Ultraviolet‐B Radiation

Abstract: Concern has been raised about the projected depletion of stratospheric o~ne and the resultant increased exposure of crops to traviolet (UV)-B radiation. Studies done in growth chambers and greenhouses indicate that substantial decreases in photosynthetic activity and leaf area growth may result from enhanced exposure to UV-B radiation. However, for soybean [Glycine max (L.) Merrol very few studies have been done under field conditions, and these studies either used unfiltered UV lamps or harvested only a few p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The mechanism responsible for the UV-B-induced stimulation of reproduction has been unknown until now. In earlier studies, a delay in development or negligible influence was also reported under growth chamber conditions (Sinclair et al, 1990;Saile-Mark and Tevini, 1997). We suggest that it might be related to differences on experimental conditions, because the inhibition effect by UV-B can be aggrandized in growth chamber.…”
Section: Effect Of Uv-b Radiation On Plant Growth Development and Prmentioning
confidence: 48%
“…The mechanism responsible for the UV-B-induced stimulation of reproduction has been unknown until now. In earlier studies, a delay in development or negligible influence was also reported under growth chamber conditions (Sinclair et al, 1990;Saile-Mark and Tevini, 1997). We suggest that it might be related to differences on experimental conditions, because the inhibition effect by UV-B can be aggrandized in growth chamber.…”
Section: Effect Of Uv-b Radiation On Plant Growth Development and Prmentioning
confidence: 48%
“…However, many factors, including feedbacks from rising concentrations of greenhouse gases, could delay this process (9,10). Important changes in future crop production could be associated with plant growth and development under enhanced UV-B radiation if crop plants were sensitive to increased levels of UV-B radiation (11). Numerous investigations have demonstrated that the effect of UV-B enhancements on plants includes reduction in grain yield, alteration in species competition, susceptibility to disease and changes in plant structure and pigmentation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies to examine UV-B effects on terrestrial plants using growth chambers or greenhouses (17,18). Commonly, the control treatment was one in which there was no exposure to UV-B and consequently, the environmental complex in these studies was artificial and the results obtained may not precisely simulate the field conditions (11). The studies of plants to enhanced UV-B radiation under field conditions are very important to an assessment of the responses of natural ecosystems to this stress factor (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the intensive investigations on growth and physiological responses to UV-B radiation on many field crops such as bean (Phaseolus vulgaris L.) (Deckmyn et al, 1994), maize (Zea mays L.) (Correia et al, 1998(Correia et al, , 1999Mark and Tevini, 1996), pea (Pisum sativum L.) (Day et al, 1996;Mepsted et al, 1996), rice (Oryza sativa L.) (Dai et al, 1992;Teramura et al, 1990), soybean [Glycine max (L.) Merr.] (Miller et al, 1994;Sinclair et al, 1990;Teramura et al, 1990), sunflower (Helianthus annuus L.) (Battaglia and Brennen, 2000), and wheat (Triticum aestivum L.) (Li et al, 2000;Teramura et al, 1990), several reviews have recently summarized the effects and consequences of UV-B radiation on major agricultural and horticultural crops, and nonagricultural species (Allen, 1990(Allen, , 1994Allen et al, 1998;Caldwell et al, 1998;Groth and Krupa, 2000;Krupa and Kickert, 1989;Teramura and Sullivan, 1994). The inferences from these studies and reviews are that plant sensitivities to UV-B radiation differ among species and cultivars within a species; however, little is known about the responses of cotton (Gossypium hirsutum L.), a major economic crop grown on over 32 Mha worldwide and over 5 Mha in the United States (http://www.ers.usda.gov/briefing/cotton).…”
Section: Introductionmentioning
confidence: 99%